Comparison Of The Rational Concepts Of The Philosopher Ibn Bajjah And The Philosopher Aristotle - Angela, Angela (DAS Institute, 2025)
This article is a comparative study that seeks to identify the differences, similarities and implications between Aristotle and Ibn Bajjah's concept of the perfect human being. The main source used as a reference in the study is the book Tadbir Al-Mutawahhid which is the work of Ibn Bajjah Nichomachean Ethic which is the work of Aristotle. Meanwhile, secondary sources are taken from various sources such as books, magazines and also articles that are in accordance with this research. Primary and secondary data are studied through historical and philosophical analysis (understanding and interpretation methods). The results of this study show that the concept of happiness according to Aristotle, happiness is the act of coexistence in harmony between the soul and the perfect virtue, happiness is experienced by a person when receiving pleasure (achievement), which is followed by the process of self-development in wanting and becoming something. while Ibn Bajjah said that happiness is the peak or end of all human goodness, so that the highest good can be achieved if a person can meet his physical and spiritual needs. And there is also the similarity of Aristotle and Ibn Bajjah's opinion about man, both agree that the goal of happiness is the first step towards happiness by doing good deeds with the help of reason, and the main idea is that Aristotle and Ibn Bajjah discuss metaphysics. The difference between Ibn Bajjah and Aristotle is that Aristotle includes the path to happiness, namely human goals, seeking as many blessings as possible, wisdom and rationality, while the path to happiness of Ibn Bajjah includes self-knowledge, the knowledge of Allah, the knowledge of the hereafter. and appreciation for the world. The implication of this research is that compared to today's life, we focus too much on worldly interests and end up forgetting about the problems of the hereafter and facing the challenges of increasingly modern technology.